PENGEMBANGAN E-LKPD MENGGUNAKAN LIVEWORKSHEET BERBASIS RADEC BERBANTUAN MIND MAP PADA SISTEM PERNAPASAN MANUSIA DI KELAS V SEKOLAH DASAR - Indah Kartika; Risda Amini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The lack of utilization and use of technology in accordance with the times and the less varied appearance of LKPD causes the appearance of LKPD that is less attractive so that students are less motivated, less creative, less initiative to express opinions, and less collaborative in working on LKPD. Therefore, this research was carried out with the aim of developing E-LKPD using RADEC-based Liveworksheets assisted by Mind Map . This research is a Research and Development (R&D) research using a 4D model. With the Define (define), Design (design, Develop, and Disseminate (spread) stages. Data from this study was obtained from the results of validation, and practicality. The validation sheet is filled out by material, language and media experts. Meanwhile, the practicality sheet is filled in by teachers and students. Then the trial was carried out in class V, namely SDN 02 Lubuk Alung by 28 students and at SDN 15 Lubuk Alung by 28 students. The results of this study produced LKPD in the form of E-LKPD using RADEC-based Liveworksheets assisted by Mind Map that are valid and practical. The overall validation results obtained a percentage of 94.77% with the category